Paul's Rhetorical use of Complex Metaphors in 1 Corinthians 3-4 - Komaravalli, Suraj Kumar (Department of Religious Studies, 2014)
After Paul had established the Corinthian church, in his absence he expected that the Corinthian congregation would enrich themselves spiritually. However, he received information that dissension and factions had erupted in the church (1:11). These factions questioned and opposed Paul's authority in the Corinthian church as the socially prominent Corinthian Christians followed and supported various other leaders whom they attributed with a greater degree of sophistic wisdom than Paul. Paul is thus faced with the challenge to address the problems of authority and factionalism in the Corinthian church. Paul addresses these issues succinctly by the use of complex metaphors. The purpose of this thesis consists of examining and discussing the manner in which Paul addresses the problems of authority and factionalism in 1 Corinthians 3-4 by the use of complex metaphors. Three major points of the thesis reflect the method of study: 1. The use of blending theory to interpret Paul's use of complex household and building metaphors as seen through the following submetaphors: i. Mother-infants relationship in antiquity (1 Cor. 3:1-4). ii. Master-servants; Planter-field; and one who waters-field relationships in antiquity (1 Cor. 3:5-9b). iii. Master builder-builders; temple-community relationship in antiquity (1 Cor. 3:9c-17). iv. Master-servants and stewards relationship in antiquity (1 Cor. 4:1-13). v. Father-children relationship in antiquity (1 Cor. 4:14-21). 2. The use of socio-rhetorical criticism to understand the social and cultural textures of the submetaphors so as to identify the features of the source domains and to 9 apply the blending theory to blend features of source domains onto target domains for interpretation of complex metaphors. 3. The use of Thompson's modes of operation of ideology to see how Paul ideologically re-establishes and sustains his dominance in the Corinthian church.